Evaluating the Cyberchondria Construct Among Computer Engineering Students in Pune (India) Using Cyberchondria Severity Scale (CSS-15). - Dagar, Deepika; Kakodkar, Pradnya; Shetiya, Sahana Hegde (Indian Journal of Occupational & Environmental Medicine)
Background: The Internet has become an important tool in day-to-day life. Reading medical data from Internet sources can have a negative impact on the common man. Anxiety due to excess searching for medical information online is known as cyberchondria. Aim: To evaluate the cyberchondria construct among the computer engineering students in Pune (India) using Cyberchondria Severity Scale (CSS-15). Settings and Design: A cross-sectional study was conducted among third- and fourth-year computer engineering students. Methods: The study recruited 180 students. A self-administered, English-translated CSS-15 questionnaire was used to collect the data. The responses were based on the Likert scale. Four constructs were scored from 0 to 4 while the mistrust of medical professional construct was scored in reverse order. Statistical Analysis: Descriptive statistics in the form of numbers and percentages were calculated. Results: The survey was completed by 171 (95%) participants, 77 females and 94 males with the mean age of 19.77 ± 1.07 years. All (100%) participants were affected by excessiveness and reassurance construct, 92% by distress, and 75% by compulsion. Only 19% were found to be affected by mistrust of a medical professional. Among all the domains, reassurance was severely affected among 52.04% of the participants. Conclusion: All the computer engineering students were affected by some or the other constructs of cyberchondria. This indicates that the Internet can affect an individual's mental, physical, and social activity by giving a vast amount of information and cause anxiety or distress related to their search.